AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN ENGLISH–INDONESIAN INTERPRETING IN THE ENGLISH EDUCATION PROGRAM AT UNIVERSITAS MUHAMMADIYAH MAKASSAR - Selma; Ilmiah; Hilda Hafid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Interpreting is an essential skill for students in English Education Programs, particularly in multilingual contexts such as Indonesia where English is learned as a foreign language. In academic and professional settings, students are required to interpret spoken English into Indonesian accurately and fluently in real time. However, many students still experience difficulties that hinder their interpreting performance. This study aims to analyze the types of difficulties faced by students in English–Indonesian interpreting and to examine how these difficulties affect their performance. This research employed a descriptive qualitative method involving five seventh-semester students of the English Education Program at Universitas Muhammadiyah Makassar who had taken or were taking an interpreting course. The participants were selected purposively based on their interpreting experience. Data were collected through semi-structured interviews and analyzed using qualitative procedures consisting of data reduction, data display, and conclusion drawing. The findings show that students mainly experience linguistic difficulties, particularly limited vocabulary and complex sentence structures. Vocabulary problems include academic vocabulary, polysemy, and idiomatic expressions, while sentence structure difficulties involve long sentences, passive constructions, and dense noun phrases. These difficulties increase students’ cognitive load and negatively affect accuracy and fluency. This study concludes that linguistic competence plays a crucial role in English–Indonesian interpreting, and interpreting instruction should emphasize vocabulary development and strategies for processing complex sentence structures.